Facts and Frequently Asked Questions About Lean, Finely-Textured Beef - Chad Carr; Dwain Johnson; Joel Brendemuhl; Larry Eubanks (EDIS, 2012)
Two very similar finely textured beef products available commercially and produced from slightly different patented processes have received an increased amount of media attention recently, where they have been referred to as “pink slime.” This 4-page fact sheet is intended to answer some of the consumer questions that have arisen as a result of this increased attention. Written by Chad Carr, Dwain Johnson, Joel Brendemuhl, and Larry Eubanks, and published by the UF Department of Animal Science, July 2012.